Experimental investigation of the influence of boiling-induced ageing on high heat flux flow boiling in a copper microchannel. (December 2021) - L, Rishi Ramakrishnan; Jayaramu, Prasanna; Gedupudi, Sateesh; Das, Sarit K.
Highlights: Experimental investigation of flow boiling of water in a copper microchannel for heat fluxes up to 3100 kW/m 2 . Boiling-induced ageing reduced the heat transfer coefficient by up to 70%. Repeated boiling runs resulted in no significant change in the critical heat flux. EDS analysis, confocal microscopy and SEM imaging of the fresh and aged channel surfaces were done. In situ measurement of contact angle on the channel surface indicated increased wettability due to ageing. Existing correlations for the critical heat flux were assessed. Abstract: Copper, due to its ease of machining and high thermal conductivity, is the most commonly used substrate for heat sink applications. This paper presents an experimental investigation of the effect of boiling-induced copper ageing on the heat transfer and critical heat flux (CHF) characteristics of flow boiling of water in a mini/micro-channel. Ageing study was conducted for two cases; Case-1 consists of repeated boiling runs in a channel with freshly machined copper surface for a constant mass flux, and Case-2 consists of repeated boiling runs in the same channel with the copper surface obtained after cleaning the aged surface with 0.1 M HCl solution. A unique feature of the test section design is that the microchannel, which is 0.47 mm deep, 1.01 mm wide and 40 mm long, has been machined on the PEEK cover plate. This enables the in-situ measurement of contact angle on the channel copper surface, which is heated and undergoes ageing during the course of the experimental runs. The heat transfer coefficient reduces by up to 63% and 70% for Case-1 and Case-2, respectively. However, the results of both Case-1 and Case-2 indicate no significant change in the CHF due to repeated boiling runs. The EDS analysis of the channel copper surface indicates thermal oxidation during ageing, and the SEM and confocal microscopy analyses show the change in surface morphology due to ageing. The results of the contact angle measurement indicate that the copper surface becomes hydrophilic after ageing. The average static contact angle on the surface reduced from 91 ο to 32 ο during the Case-1 study and from 98 ο to 28 ο during the Case-2 study. The possible reasons for the reduction in the boiling heat transfer coefficient and insignificant change in the CHF are discussed. Experiments were also carried out to study the effect of mass flux on the CHF using the fully aged channel. The CHF was found to increase with the increase in mass flux. The study compares the obtained experimental CHF values with the predictions made by the correlations available in literature.